Consortium based Biosurfactant development for degradation and emulsification of oils and Petroleum Hydrocarbons (International Journal of Engineering and Computer Science, 2017)
To develop the consortium three bacterial strains were used namely, Pseudomonas aeruginosa, Bacillus subtilis and Serratia marscecens. Among the three Serratia marscecens yielded high quantity of biosurfactant obtained after partial purification. Emulsification activity was determined from 0h to 96h for Poly aromatic hydrocarbon (against Petrol, Diesel, Mobil oil, Kerosene) and vegetable oils (Mustard oil, Soybean oil, Coconut and Jasmine oil). Among the hydrocarbons most efficient emulsification by three bacterial strains and consortium was seen for mobil oil then kerosene and petrol while diesel was least emulsified but consortium biosurfactant emulsified Diesel and was stable till 96h. Among vegetable oils highly emulsified oil was mustard and soy bean followed by Coconut and Jasmine. The study revealed the emulsification capacity of biosurfactant from consortium for poly aromatic hydrocarbons and vegetable oils.